The Essence of Aylol Revolution in Egyptian Press during the Reign of Abdul Kareem Qasim (1961-1963) - Zayed, Mahmoud M. (Humanities Journal of University of Zakho, 2016)
The research discusses the reflection of the events of Aylol Revolution in the Egyptian government press during the reign of Abdul KarimQasim, and the impact on the Egyptian Kurdish relations, the Egyptian-Iraqi relations. Egyptian newspapers broke the cases of cover-up and denial, which the Iraqi regime used them at the beginning of Aylol Revolution, and made the voice of Aylol Revolution spread to Arab and international. It said that what Kurds done in the 1961 is Kurdish revolt against the wrong policies of Abdul KarimQasim, and get on rights for the Kurdish people in the national autonomy within the unity of the political borders of Iraq.